Representação descritiva das partituras da Orquestra Amazonas Filarmônica - Costa, Anne Rafaella Correa Carvalho (Brasil, 2023)
Sheet music is a musicographic document that has different information, some elements are clearly present, others need interpretation by the professional who will technically process the work. Because of this, the organization of collections specialized in sheet music is carried out by orchestral archivists who are trained in music, who end up creating their own method of descriptive representation of scores. The lack of an adequate treatment can make it difficult for users to retrieve this document. Based on the guiding question "What elements are necessary for the Descriptive Representation of scores in the regional context?", the present work has as its general objective to identify the elements necessary for the descriptive representation of scores in the regional context, more specifically in the context of the Amazonas Philharmonic Orchestra. Given the goal, it was established as specific objectives: (a) to examine the characteristics of the sheet music document; (b) to identify the elements necessary for the descriptive representation of sheet music; (c) to compare models of descriptive representation of sheet music and the reality found in the field research. The study is exploratory and descriptive in nature. It is a bibliographic research with a qualitative-quantitative approach. To meet the proposed objectives, the structure of this work begins by presenting the concept of musical document, showing the basic characteristics of a score and its typologies, as well as the descriptive elements used during the representation process. This is followed by the methodological procedures of the research, the results, and the discussion of the data obtained from the data collection instruments applied. We conclude that the cataloging system adopted by the archival team of the collection works for the internal public, since they can retrieve the scores quickly according to the requests of the conductor and musicians, but it is important to make the partnership of the librarianship and musical area to expand the options of retrieval systems of musical information.